Effects of Acacia honey drink after exercise-induced dehydration on selected physiological parameters and subsequent running performance - Aidi-Naim Mohamad Samsani; Foong, Kiew Ooi; Chee, Keong Chen; Mohamed Saat Ismail (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study examined the effect of honey supplementation on exercise performance and biochemical markers in comparison to plain water and sports drink in the heat. Ten recreational athletes (Age: 22.2 ± 2.0 years, weight: 65.7 ± 5.3 kg; height: 170.4 ± 3.5 cm; VO2max: 51.5 ± 3.7 mL.kg−1.min−1) participated in this study. Participants ran at 70% of their VO2max for 1 h in a pre-load phase (Run-1), followed by a rehydration phase for 2 h and then a 20 min self-paced time trial (Run-2). After Run-1, participants drank either Acacia honey, sports drink or plain water with an amount equivalent to 150% of body weight loss. Subsequently, the participants performed the 20 min self-paced time trial. Acacia honey elicited an improved running time trial performance with a significantly (p<0.05) longer distance ran compared to plain water trial, but it was not different from the sports drink trial. In addition, there was no significant difference in running performance between sports drink and plain water trials. Plasma glucose, insulin and free fatty acids were significantly (p<0.05) higher in H and sports drink compared to the W trial during the rehydration phase. There were no significant differences in body weight changes, oxygen uptake, heart rate, rate of perceived exertion, tympanic temperature, plasma volume changes, plasma cortisol, urine osmolality, volume, and specific gravity among the three trials. Thus, Acacia honey can be recommended to be used as a rehydration drink for individuals who train and compete in the heat.